Torsion of a Wandering Spleen - El Bouhaddouti, Hicham (Medknow Publications, 2010)
Wandering spleen is a rare condition defined as a mobile spleen only attached with its pedicle. It can be complicated by a volvulus, which is a surgical abdominal emergency. Preventing infarction is the aim of a prompt surgery that can preserve the spleen and then proceed to splenopexy. We report a rare case of torsion of a wandering spleen associated with a dolichosigmoïd.